2011
DOI: 10.1111/j.1439-0531.2011.01791.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gamete Co‐incubation Length on the In Vitro Fertility and Sex Ratio of Bovine Bulls with Different Penetration Speed

Abstract: The objectives of this work were to evaluate whether the sperm penetration speed is correlated to the in vitro fertility and whether adapting the gamete co-incubation length to the kinetics of the bull improves in vitro fertility and affects the sex ratio. In vitro matured oocytes were co-incubated with spermatozoa from four different bulls (A-D). At various post-insemination (p.i.) times (4, 8, 12, 16 and 20 h), samples of oocytes were fixed and stained with DAPI for nuclei examination, while the remaining on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…Furthermore, IVF was carried out on abattoirderived cumulus-oocyte-complexes that were in vitro matured, fertilised and cultured according to our standard procedure (Sattar et al 2011). In particular, frozen-thawed sperm from each ejaculate were separated by Percoll gradients and used at the concentration of 1 Â 10 6 sperm/mL to inseminate on average 225 oocytes, over 4 replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, IVF was carried out on abattoirderived cumulus-oocyte-complexes that were in vitro matured, fertilised and cultured according to our standard procedure (Sattar et al 2011). In particular, frozen-thawed sperm from each ejaculate were separated by Percoll gradients and used at the concentration of 1 Â 10 6 sperm/mL to inseminate on average 225 oocytes, over 4 replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies estimated the overall temperature-mortality relationship using non-linear distributed lags and two-dimensional spline functions, and then tested the sensitivity of this parameterization [10,20]. Other studies used less complex linear and/or non-linear exposure response relationships, with a small number of lag days of between 1 and 3 [6,8,9,13,21].…”
Section: Introductionmentioning
confidence: 99%
“…Polyspermia significantly increased with the prolongation of fertilization time (P<0.05). Sattar et al, (2011) and Long et al, (1994) confirmed that too long fertilization time leads to the increase in polyspermia. The length of time IVF is associated with the occurrence of aneuploidy (Gould and Griffin, 2018).…”
Section: Ram Sperm Transformation After Incubationmentioning
confidence: 65%
“…It is possible for each species to have different needs in incubation time, caused by species specific. However, the prolongation of incubation time increases the incident of polyspermia (Sattar et al, 2011). The understanding of tranformation process of sheep sperm is necessary to increase the fertilization rate and decrease polyspermia that which cause the increasing of embryo development rate.…”
Section: Introductionmentioning
confidence: 99%